Cheshire, Fifoot and Furmston's law of contract - Furmston, M. P. (Oxford University Press, 2001)
This book provides an] account of the principles of the law of contract with ... analysis and insights ... Each topic is clearly signposted with summaries, introductory text and sub-headings for ease of navigation throughout the book. Numerous references to additional primary and secondary sources take the reader even further into the subject."-- Provided by publisher